COMPARISON OF PROPOLIS EFFECTS ON TUMOR NECROSIS FACTOR ALPHA AND MALONDIALDEHYDE BETWEEN INHALATION AND CUTANEOUS ANTHRAX ANIMAL MODELS - Harioputro, Dhani Redhono; Sanjaya, Wisnu; Werdiningsih, Yulyani (African Journal of Infectious Diseases (AJID), 2021)
Background: Inflammatory response and oxidative stress can be found in anthrax characterized by increased level of serum Tumor Necrosis Factor Alpha (TNF-α) and Malondialdehyde (MDA). The use of antibiotics in anthrax has been known to cause some disturbing side-effects, such as allergic reaction, nausea, vomiting, and antibiotic resistance. Thus, ethanolic extract of propolis (EEP) might be the alternative regimen, due to its anti-inflammatory and antioxidant properties. This study aimed to compare the effects of ethanolic extract of propolis (EEP) on TNF-α and MDA between the inhalation and cutaneous anthrax animal model. Materials and Methods: This was an experimental study with a post-test-only control group design on 40 samples of Rattus norvegicus. Samples were randomized into 5 groups: control, inhalation anthrax model, inhalation anthrax model + EEP, cutaneous anthrax model, and cutaneous anthrax model + EEP. After 14 days, the level of TNF-α and MDA were measured. To compare the data, we used the ANOVA test continued by the post-hoc Turkey test. Results: The results obtained showed that the level of TNF-α and MDA between the inhalation and cutaneous anthrax animal models treated with EEP were statistically different (p < 0.05). The P5 group showed the lowest level of TNF-α (6.822 ± 0.383 pg/ml) and MDA (2.717 ± 0.383 nmol/ml). Conclusion: EEP has a better effect on reducing TNF-α and MDA in cutaneous anthrax animal models compared to the inhalation anthrax animal model.